Metal M-doped layered Cu-based catalyst as well as preparation method and application thereof

By doping metal M in the Cu-based catalyst and adopting a layered structure design, the stability and activity problems of Cu-based catalysts in the preparation of methanol by hydrogenation of CO2 are solved, and efficient and stable catalytic performance is achieved.

CN119549140APending Publication Date: 2025-03-04CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411885527.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the process of hydrogenation of CO2, existing Cu-based catalysts have disadvantages such as easy sintering of active metal Cu, low low-temperature catalytic activity, and easy separation of Cu and support ZnO in the process of preparing methanol, which affects the stability and activity of the catalyst.

Method used

The metal M doped layered Cu-based catalyst is used, which includes the active component Cu and a Cu-supported support. The support is Zn oxide, Al oxide and metal M oxide. The structure and performance of the catalyst are controlled by doping and preparing methods of different metal M (such as constant pH method, colloid milling method, urea-acetone method or hydrothermal synthesis method).

Benefits of technology

The catalytic activity and thermodynamic stability of the catalyst are improved, the microstructure regulation of Cu and the electronic characteristics regulation of the metal-support interface are enhanced, and the selectivity and stability of methanol prepared by COx hydrogenation are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a metal M-doped layered Cu-based catalyst as well as a preparation method and application thereof. According to the invention, copper salt, zinc salt, aluminum salt and metal M salt are used as raw materials, and the active metal Cu in the prepared catalyst is highly dispersed and still keeps an intercalation structure through the controllable characteristics of element composition, structural topological transformation and the like of the metal M doped layered Cu-based catalyst. Besides, through doping of different metals M, a metal-carrier interface structure, oxygen vacancy concentration and quantity, alkaline sites, Cu metal size and the like in the catalyst are changed, so that the catalytic activity is improved. Moreover, Cu in the metal M-doped layered Cu-based catalyst prepared by different methods is good in dispersity, and when the metal M-doped layered Cu-based catalyst is used for preparing methanol through COx (x = 1 and / or 2) hydrogenation, the metal M-doped layered Cu-based catalyst has excellent stability, catalytic activity and relatively high selectivity, and can be popularized and applied to various heterogeneous catalytic reaction fields such as hydrogenation, dehydrogenation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a metal M-doped layered Cu-based catalyst and a preparation method and application thereof. Background Art

[0002] In recent years, the large-scale exploitation and use of coal, oil, natural gas and other materials have led to the emission of large amounts of greenhouse gas CO2, which has had a great impact on climate change (global warming, sea level rise, acid rain). Among them, carbon dioxide, as a renewable carbon source, has the advantages of low price, abundant reserves, safety and environmental protection. Therefore, it is an important way to reduce the above environmental problems.

[0003] However, carbon dioxide itself is chemically inert and has a strong carbon-oxygen bond energy, which makes dissociation and conversion difficult and requires the help of high-energy substances (such as H2). Therefore, the CO2 hydrogenation reaction has attracted widespread attention. At present, the reaction of CO2 and H2 into methanol can effectively reduce CO2 and store H2. At the same time, methanol, as an important chemical substance, can be widely used in various fields, such as agriculture, chemical industry and medicine. In addition, methanol, as a chemical raw material, can also be used to produce downstream products such as formaldehyde, formic acid and olefins.

[0004] However, there are many difficulties in synthesizing methanol from CO2 and H2. For example, the hydrogenation of CO2 to produce methanol is an exothermic reaction, which requires a relatively low reaction temperature, but CO2 activation requires a relatively high temperature, so it is necessary to find a suitable reaction temperature. In addition, the lack of efficient catalysts is also a major bottleneck in the hydrogenation of CO2 to produce methanol.

[0005] At present, Cu-based catalysts have mild hydrogen dissociation ability and are widely used in CO2 hydrogenation to methanol reaction due to their low cost and ability to be used at higher reaction temperatures and pressures. Among them, the common CuZnAl catalyst has high methanol selectivity and can effectively catalyze the conversion of CO2 into methanol. However, it has its own shortcomings such as easy sintering of active metal Cu, low low-temperature catalytic activity of Cu, and easy separation of Cu and carrier ZnO, which affect the stability of the catalyst and thus affect the high activity and selectivity of Cu-based catalysts for methanol. Summary of the invention

[0006] In view of this, the object of the present invention is to provide a metal M-doped layered Cu-based catalyst and a preparation method and application thereof. The catalyst has high catalytic activity and thermodynamic stability.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a metal M-doped layered Cu-based catalyst, which comprises an active component Cu, and a carrier for supporting the active component Cu; the carrier comprises Zn oxide, Al oxide and an oxide of metal M;

[0009] The metal M is selected from any one or more of Mg (magnesium), La (lanthanum), Ce (cerium), Sm (samarium), Zr (zirconium), In (indium), Ga (gallium), Sc (scandium), Y (yttrium) or Nd (neodymium). It can be seen that the doped metal M has multiple valence states, including not only divalent metals, but also trivalent metals, tetravalent metals or pentavalent metals, etc.

[0010] Preferably, the ratio of the molar amount of divalent ions in the catalyst to the total molar amount of divalent or higher ions is (1-6):1.

[0011] Preferably, in the catalyst, the doping amount of metal Cu is 0.1-90 wt%.

[0012] Preferably, in the catalyst, the doping amount of metal Zn is 0.1~80 wt%.

[0013] Preferably, in the catalyst, the doping amount of metal Al is 0.1-40 wt%.

[0014] Preferably, in the catalyst, the doping amount of the metal M is 0.1-40 wt%.

[0015] Preferably, the metal M-doped layered Cu-based catalyst has a nano-scale layered structure.

[0016] In a second aspect, the present invention provides a method for preparing the above-mentioned metal M-doped layered Cu-based catalyst, comprising the following steps:

[0017] S1: mixing a copper source, a zinc source, an aluminum source, a metal M source and a solvent to obtain a mixed solution;

[0018] S2: after mixing the precipitant with the mixed solution, a catalyst precursor of a layered multi-metal hydroxide is prepared by any one of a constant pH method, a colloid mill method, a urea-acetone method or a hydrothermal synthesis method;

[0019] S3: subjecting the catalyst precursor obtained in step S2 to a structural topological transformation treatment and a reduction treatment to obtain a metal M-doped layered Cu-based catalyst.

[0020] Preferably, the copper source includes any one or more of copper nitrate and its hydrate, copper chloride or copper acetate.

[0021] Preferably, the zinc source includes any one or more of zinc nitrate and its hydrate, zinc acetate or zinc chloride.

[0022] Preferably, the aluminum source includes any one or more of aluminum nitrate and its hydrate, aluminum chloride hexahydrate, anhydrous aluminum chloride or aluminum oxide.

[0023] Preferably, the magnesium source comprises magnesium nitrate and its hydrate and / or magnesium chloride.

[0024] Preferably, the lanthanum source includes any one or more of lanthanum nitrate and its hydrate, lanthanum chloride, lanthanum sulfate or lanthanum oxide.

[0025] Preferably, the cerium source includes any one or more of cerium nitrate and its hydrate, cerium oxide, cerium chloride or cerium sulfate.

[0026] Preferably, the samarium source comprises samarium nitrate and its hydrate and / or samarium chloride.

[0027] Preferably, the zirconium source includes any one or more of zirconium nitrate and its hydrate, zirconium oxynitrate or zirconium acetylacetonate.

[0028] Preferably, the indium source includes any one or more of indium nitrate and its hydrate, indium chloride, indium sulfate or indium oxide.

[0029] Preferably, the gallium source includes any one or more of gallium nitrate and its hydrate, gallium chloride or gallium oxide.

[0030] Preferably, the scandium source includes any one or more of scandium nitrate and its hydrate, scandium chloride or scandium oxide.

[0031] Preferably, the yttrium source includes any one or more of yttrium nitrate and its hydrate, yttrium chloride or yttrium oxide.

[0032] Preferably, the neodymium source includes any one or more of neodymium nitrate and its hydrate, neodymium chloride or neodymium oxide.

[0033] Preferably, the precipitant is selected from urea or mixed alkali.

[0034] In the present invention, the precipitant plays the role of adjusting pH and forming a precipitate after contacting with the metal in the mixed solution.

[0035] Preferably, the mixed alkali comprises a hydroxide-containing alkaline compound and a carbonate; the molar ratio of the hydroxide-containing alkaline compound to the carbonate is (0.1-5):1.

[0036] Preferably, the hydroxide-containing alkaline compound comprises sodium hydroxide and / or potassium hydroxide.

[0037] Preferably, the carbonate comprises sodium carbonate and / or potassium carbonate.

[0038] Preferably, the molar ratio of the urea to the metal ions in the mixed solution is (7-28):1.

[0039] Preferably, the molar ratio of the carbonate in the mixed alkali to the metal ions in the mixed solution is (6-8):1.

[0040] In the present invention, the specific process of the above-mentioned constant pH method and colloid mill method comprises the following steps:

[0041] (1) mixing a copper source, a zinc source, an aluminum source, a metal M salt and water to obtain a mixed salt solution; mixing a hydroxide-containing alkaline compound, a carbonate and water to obtain a mixed alkaline solution;

[0042] (2) Controlling the pH value, mixing the mixed salt solution and the mixed alkali solution obtained in the above step again, and then subjecting them to crystallization / colloid grinding to obtain a catalyst precursor of a layered double metal hydroxide.

[0043] In the present invention, the specific process of the above-mentioned urea-acetone method comprises the following steps:

[0044] (1) mixing a mixed solution of a copper source, a zinc source, an aluminum source, a metal M salt and a urea aqueous solution to obtain a mixed solution;

[0045] (2) The mixed solution obtained in the above step is crystallized to separate the solid phase, and the solid phase is mixed with acetone again and washed with acetone to obtain a catalyst precursor of a layered double metal hydroxide.

[0046] In the present invention, the specific process of the hydrothermal synthesis method comprises the following steps:

[0047] A mixed solution of a copper source, a zinc source, an aluminum source, a metal M salt and a solvent is subjected to a hydrothermal reaction and then crystallized to obtain a catalyst precursor of a layered double metal hydroxide.

[0048] Preferably, the temperature of the structural topology transformation treatment is 50-800°C.

[0049] Preferably, the time for the structural topology transformation treatment is 0.5 to 48 h.

[0050] Preferably, the temperature of the reduction treatment is 150-800°C.

[0051] Preferably, the pressure of the reduction treatment is 0.1-10 MPa.

[0052] Preferably, the reduction treatment is performed in a reducing atmosphere.

[0053] Preferably, the reducing atmosphere comprises a reducing gas and an optional protective gas; that is, the reducing atmosphere is a single reducing gas, or a mixed gas of a reducing gas and a protective gas, the reducing gas comprises any one or more of hydrogen, methane or ammonia, and the protective gas can be selected from gases well known to those skilled in the art, such as nitrogen.

[0054] In a third aspect, the present invention provides a metal M-doped layered Cu-based catalyst in CO x (x=1 and / or 2) Application in the hydrogenation reaction to produce methanol.

[0055] Compared with the prior art, the present invention has the following beneficial effects:

[0056] The present invention uses copper salt, zinc salt, aluminum salt, and metal M salt as raw materials, and adopts constant pH method, colloidal mill method, urea method-acetone method or hydrothermal synthesis method to prepare in the presence of a precipitant to obtain a metal M-doped layered Cu-based catalyst. The preparation method provided by the present invention utilizes the adjustable metal elements of hydrotalcite to form a layered multi-metal hydroxide precursor, and after the structural topological transformation (entropy change), a solid solution is formed. The active metal Cu in the obtained catalyst is highly dispersed and still maintains an intercalation structure, thereby realizing the microstructure regulation of Cu in the Cu-based catalyst. In addition, the present invention changes the metal-support interface structure, oxygen vacancy concentration and quantity, alkaline sites, and Cu metal size in the catalyst by doping with different metals, thereby improving the catalytic activity. In addition, the metal M-doped layered Cu-based catalyst prepared by different methods has good Cu dispersion, and the metal-support interface (wherein the metal is Cu, and the support refers to a mixed metal oxide of zinc oxide, aluminum oxide, and metal M oxide) structural electronic properties are adjustable, and it is used for CO x (x=1 and / or 2) When hydrogenating to prepare methanol, it has excellent stability, catalytic activity and high selectivity, and can be widely used in various multiphase catalytic reaction fields such as hydrogenation and dehydrogenation. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 The SEM and Mapping images of Cu-S1-Mg-LDH, the precursor of the Cu-S1-Mg catalyst in Example 1;

[0058] Figure 1 a is the SEM image of the catalyst precursor. Figure 1 b is the mapping diagram of the catalyst precursor. Figure 1 c is the mapping diagram of Cu element in the catalyst precursor, Figure 1 d is the mapping diagram of Zn element in the catalyst precursor. Figure 1 e is the mapping diagram of Al element in the catalyst precursor. Figure 1 f is the mapping diagram of Mg element in the catalyst precursor;

[0059] Figure 2 The SEM and Mapping images of the catalyst precursor Cu-S1-Sm-LDH of Cu-S1-Sm in Example 1;

[0060] Figure 2 a is the SEM image of the catalyst precursor. Figure 2 b is the mapping diagram of the catalyst precursor. Figure 2 c is the mapping diagram of Cu element in the catalyst precursor, Figure 2 d is the mapping diagram of Zn element in the catalyst precursor. Figure 2 e is the mapping diagram of Al element in the catalyst precursor. Figure 2 f is the mapping diagram of Sm element in the catalyst precursor;

[0061] Figure 3 The SEM and Mapping images of the Cu-S1-Zr catalyst precursor Cu-S1-Zr-LDH in Example 1;

[0062] Figure 3 a is the SEM image of the catalyst precursor. Figure 3 b is the mapping diagram of the catalyst precursor. Figure 3 c is the mapping diagram of Cu element in the catalyst precursor, Figure 3 d is the mapping diagram of Zn element in the catalyst precursor. Figure 3 e is the mapping diagram of Al element in the catalyst precursor. Figure 3 f is the mapping diagram of Zr element in the catalyst precursor;

[0063] Figure 4 The SEM and Mapping images of Cu-S1-Mg-MMO in Example 1;

[0064] Figure 4 a is the SEM image, Figure 4 b is the overall Mapping diagram, Figure 4 c is the mapping diagram of Cu element, Figure 4 d is the mapping diagram of Zn element, Figure 4 e is the mapping diagram of Al element, Figure 4 f is the mapping diagram of Mg element;

[0065] Figure 5 The SEM and Mapping images of Cu-S1-Sm-MMO in Example 1;

[0066] Figure 5 a is the SEM image, Figure 5 b is the overall Mapping diagram, Figure 5 c is the mapping diagram of Cu element, Figure 5 d is the mapping diagram of Zn element, Figure 5 e is the mapping diagram of Al element, Figure 5 f is the Mapping graph of Sm elements;

[0067] Figure 6 The SEM and Mapping images of Cu-S1-Zr-MMO in Example 1;

[0068] Figure 6 a is the SEM image, Figure 6 b is the overall Mapping diagram, Figure 6 c is the mapping diagram of Cu element, Figure 6 d is the mapping diagram of Zn element, Figure 6 e is the mapping diagram of Al element, Figure 6 f is the Mapping diagram of Zr element;

[0069] Figure 7 The SEM and Mapping images of the Cu-S1-Mg catalyst in Example 1;

[0070] Figure 7 a is the SEM image, Figure 7 b is the mapping diagram of the catalyst, Figure 7 c is the mapping diagram of Cu element in the catalyst, Figure 7 d is the mapping diagram of Zn element in the catalyst, Figure 7 e is the mapping diagram of Al element in the catalyst, Figure 7 f is the mapping diagram of Mg element in the catalyst;

[0071] Figure 8 The SEM and Mapping images of the Cu-S1-Sm catalyst in Example 1;

[0072] Figure 8 a is the SEM image of the catalyst. Figure 8 b is the mapping diagram of the catalyst, Figure 8 c is the mapping diagram of Cu element in the catalyst, Figure 8 d is the mapping diagram of Zn element in the catalyst, Figure 8 e is the mapping diagram of Al element in the catalyst, Figure 8f is the mapping diagram of the Sm element in the catalyst;

[0073] Fig. 9 The SEM and Mapping images of the Cu-S1-Zr catalyst in Example 1;

[0074] Fig. 9 a is the SEM image of the catalyst. Fig. 9 b is the mapping diagram of the catalyst, Fig. 9 c is the mapping diagram of Cu element in the catalyst, Fig. 9 d is the mapping diagram of Zn element in the catalyst, Fig. 9 e is the mapping diagram of Al element in the catalyst, Fig. 9 f is the mapping diagram of Zr element in the catalyst;

[0075] Fig.10 XRD of Cu-S1-M (M=Mg, Sm, Zr) catalyst in Example 1;

[0076] Fig.11 This is the XRD of the Cu-S1-M catalyst precursor Cu-S1-M-LDH (M=Mg, Sm, Zr) in Example 1. DETAILED DESCRIPTION

[0077] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0078] The present invention provides a metal M-doped layered Cu-based catalyst, which comprises an active component Cu and a carrier for supporting the active component Cu;

[0079] The support is a mixed metal oxide, including Zn oxide, Al oxide and metal M oxide.

[0080] In the present invention, the metal M is in a multivalent state, and can be specifically selected from any one or more of Mg (magnesium), La (lanthanum), Ce (cerium), Sm (samarium), Zr (zirconium), In (indium), Ga (gallium), Sc (scandium), Y (yttrium) or Nd (neodymium), preferably any one or more of Mg, La, Ce, Sm, Y or Nd, and more preferably any one or more of Sm, Zr or Mg.

[0081] In the present invention, after the above metals Mg, La, Ce, Sm, Y, and Nd are doped in the catalyst, the oxide formed after the structural topological transformation has alkalinity and can provide alkaline sites, thereby better absorbing CO x (x=1 and / or 2).

[0082] The present invention dopes the above metals Zr, In, Ce, Sc, Ce, and Ga into the catalyst, and the oxide formed by the structural topological transformation has a specific electronic structure and can form oxygen vacancies, thereby reducing CO x (x = 1 and / or 2) adsorption activation energy, promoting the formation of methanol.

[0083] In the present invention, the ratio of the molar amount of divalent ions to the total molar amount of divalent or higher ions in the metal M-doped layered Cu-based catalyst is (1-6): 1, preferably (2-4): 1, and more preferably 2: 1. The present invention preferably controls the total molar amount ratio of divalent ions to divalent or higher ions within the above range because the layered structure formed by the catalyst precursor within the above range is more obvious.

[0084] In the present invention, in the metal M-doped layered Cu-based catalyst, the doping amount of metal Cu is 0.1-90 wt%, preferably 5-40 wt%, and more preferably 10 wt%.

[0085] In the present invention, in the metal M-doped layered Cu-based catalyst, the doping amount of metal Zn is 0.1-80 wt%, preferably 50-70 wt%, and more preferably 60-70 wt%.

[0086] In the present invention, in the metal M-doped layered Cu-based catalyst, the doping amount of metal Al is 0.1-40 wt%, preferably 10-30 wt%, and more preferably 22-28 wt%.

[0087] In the present invention, in the metal M-doped layered Cu-based catalyst, the doping amount of the metal M is 0.1-40 wt%, preferably 2-20 wt%, and more preferably 5-10 wt%.

[0088] The present invention controls the doping amounts of Cu, Zn, Al and metal M in the metal M-doped layered Cu-based catalyst in order to control its structure to be a nano-level layered structure.

[0089] The specific composition of the metal M doped layered Cu-based catalyst provided by the present invention is Cu / MZnAlO (wherein MZnAlO represents a mixed oxide of metal M oxide, Zn oxide and oxide). Due to the complex components of the catalyst, only its elemental composition is shown here.

[0090] In the present invention, the metal M doped layered Cu-based catalyst has a nano-scale layered structure. After topological transformation (entropy change), the mixed metal oxide is a solid solution and still retains a layered structure. The layered metal cations are arranged at the atomic level. The metal cations M (M = Mg, La, Ce, Sm, Zr, In, Ga, Sc, Y, Nd) are adjustable and interact with the layered anions. The doped metal M and the interlayer anions (for example: CO3 2- , Cl - 、NO 3- ) can be regulated, thereby regulating the concentration and number of oxygen vacancies, basic sites, and Cu metal size in the catalyst, thereby promoting high exposure of Cu, the formation of more oxygen vacancies and basic sites, and promoting the improvement of catalyst performance.

[0091] The present invention also provides a method for preparing the above-mentioned metal M-doped layered Cu-based catalyst, comprising the following steps:

[0092] S1: mixing a copper source, a zinc source, an aluminum source, a metal M source and a solvent to obtain a mixed solution;

[0093] S2: after mixing the precipitant with the mixed solution, a catalyst precursor of a layered multi-metal hydroxide is prepared by any one of a constant pH method, a colloid mill method, a urea-acetone method or a hydrothermal synthesis method;

[0094] S3: subjecting the catalyst precursor obtained in step S2 to a structural topological transformation treatment and a reduction treatment to obtain a metal M-doped layered Cu-based catalyst.

[0095] In the present invention, the copper source includes any one or more of copper nitrate and its hydrate (the hydrate can be selected as: copper nitrate trihydrate), copper chloride or copper acetate, preferably copper nitrate trihydrate.

[0096] In the present invention, the zinc source includes any one or more of zinc nitrate and its hydrate (the hydrate may be zinc nitrate hexahydrate), zinc acetate or zinc chloride, preferably zinc nitrate hexahydrate.

[0097] The aluminum source includes any one or more of aluminum nitrate and its hydrate (the hydrate may be aluminum nitrate nonahydrate), aluminum chloride hexahydrate, anhydrous aluminum chloride or aluminum oxide, preferably aluminum nitrate nonahydrate.

[0098] The magnesium source includes magnesium nitrate and its hydrate and / or magnesium chloride, preferably magnesium nitrate.

[0099] The lanthanum source includes any one or more of lanthanum nitrate and its hydrate, lanthanum chloride, lanthanum sulfate or lanthanum oxide, preferably lanthanum nitrate.

[0100] The cerium source includes any one or more of cerium nitrate and its hydrate, cerium oxide, cerium chloride or cerium sulfate, preferably cerium nitrate.

[0101] The samarium source includes samarium nitrate and its hydrate and / or samarium chloride, preferably samarium nitrate.

[0102] The zirconium source includes any one or more of zirconium nitrate and its hydrate, zirconium oxynitrate or zirconium acetylacetonate, preferably zirconium nitrate.

[0103] The indium source includes any one or more of indium nitrate and its hydrate, indium chloride, indium sulfate or indium oxide, preferably indium nitrate.

[0104] The gallium source includes any one or more of gallium nitrate and its hydrate, gallium chloride or gallium oxide, preferably gallium nitrate.

[0105] The scandium source includes any one or more of scandium nitrate and its hydrate, scandium chloride or scandium oxide, preferably scandium nitrate.

[0106] The yttrium source includes any one or more of yttrium nitrate and its hydrate, yttrium chloride or yttrium oxide, preferably yttrium nitrate.

[0107] The neodymium source includes any one or more of neodymium nitrate and its hydrate, neodymium chloride or neodymium oxide, preferably neodymium nitrate.

[0108] In the present invention, the precipitant is selected from urea or a mixed alkali, wherein the molar ratio of the urea to the metal ions in the mixed solution is (7-28):1, preferably (10-20):1, and more preferably (12-15):1.

[0109] In the present invention, the mixed alkali comprises a hydroxide-containing alkaline compound and / or a carbonate, wherein the molar ratio of the hydroxide-containing alkaline compound to the carbonate is (0.1-5):1, preferably (1-4):1, and more preferably 4:1.

[0110] In the present invention, the hydroxide-containing alkaline compound includes sodium hydroxide and / or potassium hydroxide, preferably sodium hydroxide; the carbonate includes sodium carbonate and / or potassium carbonate, preferably sodium carbonate. Preferably, the sum of the molar concentrations of the hydroxide-containing alkaline compound and the carbonate is 0.5 to 5 mol / L; more preferably 1 to 3 mol / L; further preferably 1.2 mol / L.

[0111] In the present invention, the molar ratio of the carbonate in the mixed alkali to the metal ions in the mixed solution is (6-8):1, preferably (6.5-7.5):1.

[0112] In the present invention, the specific process of the above-mentioned constant pH method and colloid mill method comprises the following steps:

[0113] (1) mixing a copper source, a zinc source, an aluminum source, a metal M salt and water to obtain a mixed salt solution; mixing a hydroxide-containing alkaline compound, a carbonate and water to obtain a mixed alkaline solution;

[0114] (2) Controlling the pH value, mixing the mixed salt solution and the mixed alkali solution obtained in the above step again, and then performing crystallization / colloid grinding to obtain a catalyst precursor of a layered double metal hydroxide, that is, a metal M-doped layered Cu-based catalyst precursor.

[0115] In some specific embodiments of the present invention, the constant pH method comprises the following steps:

[0116] Preferably, the Cu 2+ Copper salts, Zn 2+ Zinc salt, Al 3+ The aluminum salt and metal M salt are mixed with water as a solvent (the water can be one or more of distilled water, deionized water or ultrapure water; preferably deionized water), stirred thoroughly to dissolve them completely, and a mixed salt solution is prepared ①; the hydroxide-containing alkaline compound and carbonate are prepared into a mixed alkali solution ②. In another beaker, 10-50 mL of deionized water is added, and the mixed alkali solution and the mixed salt solution are slowly dripped into them respectively, and stirred continuously, and the pH of the suspension is controlled to 7-14 by a pH meter, preferably 7-9. After all the salt solutions are added, the suspension is moved into a constant temperature water bath, the crystallization temperature is controlled to 40-100°C, and stirred continuously for crystallization for 1-12 h. After the crystallization is completed, the solid-liquid separation is carried out, and the solid is washed with deionized water until neutral, and then the solid is placed in a constant temperature box at 30-90°C for 6-24 h to obtain a catalyst precursor of a layered double metal hydroxide.

[0117] In this technical solution, the present invention monitors the pH value of the system by a pH meter and controls it within a reasonable range, thereby ensuring that the layered polymetallic hydroxide precursor has suitable alkaline properties, thereby reducing the problem of carbon deposition and deactivation of the catalyst occurring during the hydrogenation reaction.

[0118] In some specific embodiments of the invention, the colloid milling method comprises the following steps:

[0119] Preferably, the Cu 2+ Copper salts, Zn 2+ Zinc salts, Al 3+The aluminum salt and metal M salt are mixed with water as solvent (the water can be one or more of distilled water, deionized water or ultrapure water; preferably deionized water), stirred thoroughly to completely dissolve, and a mixed salt solution is prepared ①; the hydroxide-containing alkaline compound and carbonate are prepared into a mixed alkaline solution ②. The metal salt solution and the alkaline solution are quickly added to the colloid mill reactor for mixing at a speed of 3000-10000 rpm, preferably 6000-8000 rpm, and stirred for 5-30 min. After the crystallization is completed, the solid-liquid separation is carried out, and the solid is washed with anhydrous ethanol for 1-4 times, and then the solid is placed in a constant temperature box at 40-90°C for 6-24 hours to obtain a catalyst precursor of a layered double metal hydroxide.

[0120] In the present invention, the specific process of the above-mentioned urea-acetone method comprises the following steps:

[0121] (1) mixing a mixed solution of a copper source, a zinc source, an aluminum source, a metal M salt and a urea aqueous solution to obtain a mixed solution;

[0122] (2) The mixed solution obtained in the above step is crystallized to separate the solid phase, and the solid phase is mixed with acetone again and washed with acetone to obtain a catalyst precursor of a layered double metal hydroxide.

[0123] In some specific embodiments of the present invention, the urea-acetone process comprises the following steps:

[0124] Preferably, the Cu 2+ Copper salts, Zn 2+ Zinc salt, Al 3+ Aluminum salt, metal M salt and a certain amount of urea are mixed with water as a solvent (the water can be one or more of distilled water, deionized water or ultrapure water; deionized water is preferably used), stirred fully to completely dissolve, and a mixed solution is prepared. The mixed solution is then placed in a three-necked flask, moved into a constant temperature water bath, the crystallization temperature is controlled to be 90-120°C, and stirred continuously for crystallization for 1-12 h. After the crystallization is completed, solid-liquid separation is performed, and the solid is washed with deionized water until neutral. The obtained wet cake solid sample is redispersed in 100-300 mL acetone and stirred at room temperature for 1-3 hours. Then, it is washed with acetone and dried in a constant temperature oven at 30-90°C for 6-24 h to obtain a catalyst precursor of a layered multimetal hydroxide.

[0125] In the present invention, the specific process of the hydrothermal synthesis method comprises the following steps:

[0126] A mixed solution of a copper source, a zinc source, an aluminum source, a metal M salt and a solvent is subjected to a hydrothermal reaction and then crystallized to obtain a catalyst precursor of a layered double metal hydroxide.

[0127] In some specific embodiments of the present invention, the hydrothermal synthesis method comprises the following steps:

[0128] Preferably, the Cu 2+ Copper salts, Zn 2+ Zinc salt, aluminum oxide, and metal M salt are used as solvents, stirred thoroughly to completely dissolve, and a mixed solution ① is prepared; urea is dissolved in water to prepare a mixed solution ②. Then, the mixed solution ① and the mixed solution ② are placed in the lining of the hydrothermal reactor and stirred for 1 to 4 hours, and then the reactor is moved to a constant temperature box at 90 to 120°C for crystallization for 8 to 24 hours. After the crystallization is completed, the solid-liquid separation is carried out, and the solid is washed with deionized water until it is neutral, and then the solid is placed in a constant temperature box at 30 to 90°C for drying for 6 to 24 hours.

[0129] In the present invention, the water used in the mixed solution ① and the mixed solution ② is one or more of distilled water, deionized water or ultrapure water; more preferably, deionized water is used.

[0130] In the present invention, the volume ratio of the mixed solution ① to the mixed solution ② is (0.1-5):1; more preferably (0.5-2):1. In some specific embodiments of the present invention, the volume ratio of the mixed solution ① to the mixed solution ② is 1:1.

[0131] Preferably, in the process of mixing the mixed solution ① and the mixed solution ②, the pH value of the system is controlled to remain unchanged. Specifically, the pH value can be controlled to remain unchanged by controlling the dropping speed and the stirring speed.

[0132] Preferably, the rotation speed of the "stirring" mentioned above is 3000-10000 rpm; more preferably, the rotation speed is 6000-8000 rpm.

[0133] The present invention has no particular limitation on the washing method involved in the above-mentioned preparation method, and the washing method may be a method well known to those skilled in the art, such as centrifugation, vacuum filtration, normal pressure filtration, etc.

[0134] The present invention has no particular limitation on the drying method described in the above preparation method, and it can be a method well known to those skilled in the art, such as normal pressure drying, vacuum drying, freeze drying, etc.

[0135] According to the present invention, after obtaining the catalyst precursor of the layered double metal hydroxide, a structural topological transformation treatment and a reduction treatment are performed to obtain a layered multimetal hydroxide precursor CuZnAlM-based catalyst, that is, a metal M-doped layered Cu-based catalyst.

[0136] In the present invention, the temperature of the structural topological transformation treatment is 50-800° C., preferably 200-700° C., and more preferably 500° C. The time of the structural topological transformation treatment is 0.5-48 h, preferably 1-12 h, more preferably 2-6 h, and further preferably 4 h.

[0137] The temperature of the reduction treatment is 150-800°C, preferably 200-450°C, and more preferably 250-300°C; the pressure of the reduction treatment is 0.1-10 MPa, preferably 1-5 MPa; the time of the reduction treatment is 1-10 h, preferably 2-5 h.

[0138] In the present invention, the reduction treatment is carried out in a reducing atmosphere; the reducing atmosphere includes a reducing gas and an optional protective gas, that is, the reducing atmosphere is a single reducing gas, or a mixed gas of a reducing gas and a protective gas. The reducing gas includes any one or more of hydrogen, methane or ammonia, preferably hydrogen, and the protective gas is selected from gases well known to those skilled in the art, such as nitrogen. In some embodiments of the present invention, a mixed gas of H2 and N2 is preferably used, and the volume ratio of H2 to N2 is 1:(1~10), preferably 1:(2~5).

[0139] In the present invention, the volume content of hydrogen in the reduction treatment atmosphere is 5% to 100%; more preferably, the volume content of hydrogen is 20%. Preferably, the time of the reduction treatment atmosphere is 2 to 5 hours; more preferably, the time of the reduction treatment atmosphere is 2 hours.

[0140] The preparation method provided by the present invention is simple, convenient, easy to implement, and is conducive to large-scale production or industrial production.

[0141] The present invention also provides a metal M-doped layered Cu-based catalyst in CO x (x=1 and / or 2) in the hydrogenation reaction to produce methanol. In this application, the metal M-doped layered Cu-based catalyst is used as a hydrogenation catalyst and reacts with CO x (x=1 and / or 2) and the reaction gas of H2 directly contact and react to obtain methanol and water.

[0142] The present invention is for the above-mentioned CO x (x=1 and / or 2) The reactor for the hydrogenation reaction to prepare methanol is not particularly limited and may be a fixed bed reactor.

[0143] In the present invention, the CO in the reaction gas x The volume ratio of (x=1 and / or 2) to H2 is 1:(1-6), preferably 1:(3-5). Further preferably, CO in the reaction gas xThe volume ratio of (x=1 and / or 2) to H2 is 1:3.

[0144] In the present invention, the CO x The volume flow rate of the mixed gas of (x=1 and / or 2) and H2 is 40~400 mL / min, preferably 50~300 mL / min.

[0145] In the present invention, it is preferred that the balance gas of the reaction gas is selected from one or more of nitrogen, argon and helium.

[0146] In the present invention, it is preferred that the CO x (x=1 and / or 2) The volume space velocity of hydrogenation to methanol is 4000~100000 h -1 , preferably 8000~80000 h -1 .

[0147] The present invention preferably comprises the CO x (x=1 and / or 2) The reaction temperature for hydrogenation to synthesize methanol is 180-300°C; more preferably 200-300°C. In some specific embodiments of the present invention, CO x (x=1 and / or 2) The temperature of the hydrogenation reaction is 200°C, 220°C, 230°C and 250°C, which is beneficial to reduce the side reactions caused by overheating.

[0148] The reaction pressure is preferably 0.1-10 MPa; more preferably 3-5 MPa; further preferably, the reaction pressure is 3 MPa or 4 MPa.

[0149] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products.

[0150] Example 1

[0151] 1. Preparation of Cu-S1 catalyst

[0152] Copper nitrate trihydrate, zinc nitrate hexahydrate, aluminum nitrate nonahydrate and metal M salt (magnesium nitrate hexahydrate, cedar nitrate hexahydrate and zirconium nitrate pentahydrate, respectively) were added at a molar ratio of divalent ions to (trivalent ions + tetravalent ions) of about 2:1. The molar feed ratio of copper nitrate trihydrate, zinc nitrate hexahydrate, aluminum nitrate nonahydrate and metal M salt was 20:50:29:2. Deionized water was used as the solvent, and it was fully stirred to completely dissolve to prepare 100 mL of a mixed salt solution of about 0.38 mol / L. Sodium hydroxide and sodium carbonate were prepared into a 100 mL, 1.24 mol / L mixed alkali solution, and it was fully stirred to completely dissolve. In another beaker, 50 mL of distilled water was added, and the mixed alkali solution and mixed salt solution were slowly dripped into them respectively, and stirred continuously. The pH of the suspension was controlled to 8±1 using a pH meter. After all the salt solutions were added, the suspension was transferred to a constant temperature water bath, the crystallization temperature was controlled at 60°C, and the suspension was stirred continuously for 10 h. After the crystallization was completed, the solid-liquid separation was performed, and the solid was washed with deionized water until neutral, and then the solid was placed in a 60°C constant temperature oven to dry for 12 h. The obtained catalyst precursor was a layered double metal hydroxide Cu-S1-M-LDH (M = Mg, Sm, Zr). The obtained catalyst precursor (in the form of solid powder) was further subjected to a structural topological transformation treatment, and was treated at 500°C for 4 h in an air atmosphere to obtain Cu-S1-M-MMO. Finally, the reaction mixture was heated at 300°C with a total flow rate of 100 mL min -1 , and reduced in a mixed gas of H2:N2 in a ratio of 1:4 for 2 h to obtain a layered multimetal hydroxide precursor copper-based catalyst Cu-S1 with an intercalated structure, which can be recorded as: Cu-S1-Mg, Cu-S1-Sm, and Cu-S1-Zr.

[0153] In the Cu-S1 catalyst provided in this embodiment, based on the mass of the catalyst as 100%, the mass content of Cu is 20wt%, the mass content of metal M (M=Mg, Sm, Zr) is 5wt%, the mass content of Zn is 55wt%, and the mass content of metal Al is 20wt%.

[0154] SEM test and mapping test were performed on the catalyst precursor, the catalyst obtained after structural topological transformation treatment and the catalyst obtained after reduction in this embodiment. The results are as follows Figures 1 to 9 shown.

[0155] in, Figure 1 The SEM and Mapping images of Cu-S1-Mg-LDH, the precursor of the Cu-S1-Mg catalyst in Example 1; Figure 2 The SEM and Mapping images of the catalyst precursor Cu-S1-Sm-LDH of Cu-S1-Sm in Example 1; Figure 3The SEM and Mapping images of the Cu-S1-Zr catalyst precursor Cu-S1-Zr-LDH in Example 1; Figure 4 The SEM and Mapping images of Cu-S1-Mg-MMO in Example 1; Figure 5 The SEM and Mapping images of Cu-S1-Sm-MMO in Example 1; Figure 6 The SEM and Mapping images of Cu-S1-Zr-MMO in Example 1; Figure 7 The SEM and Mapping images of the Cu-S1-Mg catalyst in Example 1; Figure 8 The SEM and Mapping images of the Cu-S1-Sm catalyst in Example 1; Fig. 9 These are the SEM and mapping images of the Cu-S1-Zr catalyst in Example 1.

[0156] XRD test was performed on the catalyst precursor and the catalyst obtained after reduction in this example. The results are as follows Figures 10-11 shown.

[0157] Fig.10 XRD of Cu-S1-M (M=Mg, Sm, Zr) catalyst in Example 1; Fig.11 This is the XRD of the Cu-S1-M catalyst precursor Cu-S1-M-LDH (M=Mg, Sm, Zr) in Example 1.

[0158] By the above Figures 1 to 9 It can be seen that from the catalyst precursor, after topological transformation, and reduction SEM and mapping images, Cu, metal M (M = Mg, Sm, Zr), Zn, and Al are uniformly dispersed in the catalyst. Figures 10-11 It can be seen from the XRD diagram that the precursors synthesized in Example 1 are all in the hydrotalcite structure, and only metal Cu exists after topological transformation and reduction, and the others exist in the form of metal oxides.

[0159] (ii) Cu-S1 catalyst catalyzes CO x (x=1 and / or 2) Hydrogenation

[0160] Weigh 0.5 g of Cu-S1 catalyst and 0.5 g of quartz sand with a mesh size of 40-60 and mix them evenly. Place the mixture in a quartz reaction tube and introduce a hydrogen-nitrogen mixture with a total volume flow rate of 100 mL / min and a hydrogen volume concentration of 20%. Pretreat at 300 °C for 2 h. After the pretreatment, turn off the H2 gas and use N2 for pressurized leak detection. After confirming that there is no leakage, turn off the N2. Introduce the mixed reaction gas (CO x(x = 1 and / or 2) / H2 / N2 = 22 / 66 / 12, volume ratio) and pressurized to 3 MPa, heated to 200 °C, and adjusted the mixed gas flow rate to 80 mL min -1 .

[0161] Reaction product monitoring: During the reaction process, the products at different reaction times were analyzed. The detection method was: after the reaction reached a steady state, the products of the reaction system were collected every 20 min.

[0162] The obtained carbon dioxide reaction rate, methanol selectivity and space-time yield are shown in Table 1.

[0163] Example 2

[0164] 1. Preparation of Cu-S2 catalyst

[0165] Copper nitrate trihydrate, zinc nitrate hexahydrate, aluminum nitrate nonahydrate and zirconium nitrate pentahydrate were added in a molar ratio of divalent ions to (trivalent ions + tetravalent ions) of 70:31. The molar feed ratio of copper nitrate trihydrate, zinc nitrate hexahydrate, aluminum nitrate nonahydrate and zirconium nitrate pentahydrate was 20:50:29:2. Deionized water was used as the solvent, and it was fully stirred to completely dissolve and prepare 100 mL of a mixed salt solution of about 0.38 mol / L. Sodium hydroxide and sodium carbonate were prepared into a 100 mL, 1.24 mol / L mixed alkali solution, and fully stirred to completely dissolve. The mixed salt solution and the mixed solution were quickly added to the colloid mill reactor for mixing, and the speed was 6000 rpm and stirred for 10 minutes. After the crystallization was completed, solid-liquid separation was performed, and the solid was washed with anhydrous ethanol 3 times. The solid was then placed in a constant temperature oven at 60°C and dried for 12 h. The catalyst precursor obtained was layered double hydroxide Cu-S1-M-LDH (M = Zr). The catalyst precursor (in the form of solid powder) was further treated with structural topological transformation to obtain Cu-S1-M-MMO, which was treated at 500 °C for 4 h and finally at 300 °C with a total flow rate of 100 mL min -1 , and reduced in a mixed gas of H2:N2 in a ratio of 1:4 for 2 h to obtain a layered multimetal hydroxide precursor copper-based catalyst Cu-S2 with an intercalated structure.

[0166] In the Cu-S2 catalyst provided in this embodiment, based on the mass of the catalyst as 100%, the mass content of Cu is 20 wt%, the mass content of metal Zr is 5 wt%, the mass content of Zn is 55 wt%, and the mass content of metal Al is 20 wt%.

[0167] (ii) Cu-S2 catalyst catalyzes CO x (x=1 and / or 2) Hydrogenation

[0168] This method is the same as the method for catalytic hydrogenation of carbon dioxide provided in Example 1, but the difference is that the catalyst is a Cu-S2 catalyst, and the rest is the same as Example 1.

[0169] The reaction product detection method is the same as that in Example 1, and the detection results are shown in Table 1.

[0170] Example 3

[0171] 1. Preparation of Cu-S3 catalyst

[0172] Copper nitrate trihydrate, zinc nitrate hexahydrate, aluminum nitrate nonahydrate and zirconium nitrate pentahydrate were added in a molar ratio of divalent ions to trivalent ions of 2:1, and the molar feeding ratio of copper nitrate trihydrate, zinc nitrate hexahydrate, aluminum nitrate nonahydrate and zirconium nitrate pentahydrate was 20:50:29:2, and urea was added, deionized water was used as a solvent, and it was fully stirred to completely dissolve and prepare a mixed solution. The mixed solution was then placed in a three-necked flask, moved into a constant temperature water bath, the crystallization temperature was controlled to 100°C, and it was continuously stirred and crystallized for 10 h. After the crystallization was completed, solid-liquid separation was performed, and the solid was washed with deionized water until neutral. The obtained wet cake solid sample was redispersed in 200 mL of acetone and stirred at room temperature for 2 hours. Then, it was washed with acetone and dried in a constant temperature box at 25°C for 12 h. The catalyst precursor obtained was layered double hydroxide Cu-S1-M-LDH (M = Zr). The solid powder was further treated with structural topological transformation to obtain Cu-S1-M-MMO, which was treated at 500 °C for 4 h and finally at 300 °C with a total flow rate of 100 mL min -1 , and reduced in a mixed gas of H2:N2 in a ratio of 1:4 for 2 h to obtain a layered multimetal hydroxide precursor copper-based catalyst Cu-S3 with an intercalated structure.

[0173] In the Cu-S3 catalyst provided in this embodiment, based on the mass of the catalyst as 100%, the mass content of Cu is 20 wt%, the mass content of metal Zr is 5 wt%, the mass content of Zn is 55 wt%, and the mass content of metal Al is 20 wt%.

[0174] (ii) Cu-S3 catalyst catalyzes CO x (x=1 and / or 2) Hydrogenation

[0175] This method is the same as the method for catalytic hydrogenation of carbon dioxide provided in Example 1, except that the catalyst used is Cu-S3 catalyst, and the rest is the same as Example 1.

[0176] The reaction product detection method is the same as that in Example 1, and the detection results are shown in Table 1.

[0177] Example 4

[0178] 1. Preparation of Cu-S4 catalyst

[0179] Copper nitrate trihydrate, zinc nitrate hexahydrate, aluminum nitrate nonahydrate and zirconium nitrate pentahydrate were added at a molar ratio of divalent ions to (trivalent ions + tetravalent ions) of 2:1, and the molar feeding ratio of copper nitrate trihydrate, zinc nitrate hexahydrate, aluminum nitrate nonahydrate and zirconium nitrate pentahydrate was 20:50:29:2. Deionized water was used as the solvent, and the mixture was fully stirred to completely dissolve to form a mixed solution ①; urea was dissolved in deionized water to form a mixed solution ②. Subsequently, the mixed solution ① and the mixed solution ② were placed in the lining of the hydrothermal reactor and stirred for 2 h, and then the reactor was moved to a constant temperature box at 100 ° C for crystallization for 24 h. After the crystallization was completed, the solid-liquid separation was carried out, and the solid was washed with deionized water until neutral, and then the solid was placed in a constant temperature box at 60 ° C for 12 h. The catalyst precursor was a layered double hydroxide, Cu-S1-M-LDH (M = Zr). The solid powder was further treated with a structural topological transformation to obtain Cu-S1-M-MMO, which was treated at 500 °C for 4 h and finally at 300 °C with a total flow rate of 100 mL min -1 , and reduced in a mixed gas of H2:N2 in a ratio of 1:4 for 2 h to obtain a layered multimetal hydroxide precursor copper-based catalyst Cu-S4 with an intercalated structure.

[0180] In the Cu-S4 catalyst provided in this embodiment, based on the mass of the catalyst as 100%, the mass content of Cu is 20 wt%, the mass content of metal Zr is 5 wt%, the mass content of Zn is 55 wt%, and the mass content of metal Al is 20 wt%.

[0181] (ii) Cu-S4 catalyst catalyzes CO x (x=1 and / or 2) Hydrogenation

[0182] This method is the same as the method for catalytic hydrogenation of carbon dioxide provided in Example 1, except that the catalyst used is Cu-S4 catalyst, and the rest is the same as Example 1.

[0183] The reaction product detection method is the same as that in Example 1, and the detection results are shown in Table 1.

[0184] Comparative Example 1

[0185] 1. Preparation of Cu-S5 catalyst

[0186] Copper nitrate trihydrate, zinc nitrate hexahydrate, and aluminum nitrate nonahydrate were added at a molar ratio of divalent ions to trivalent ions of 2:1, and deionized water was used as the solvent. They were fully stirred to completely dissolve and prepare 100 mL of a mixed salt solution of about 0.38 mol / L. Sodium hydroxide and sodium carbonate were prepared into a 100 mL, 1.24 mol / L mixed alkali solution, which was fully stirred to completely dissolve. In another beaker, 50 mL of distilled water was added, and the mixed alkali solution and mixed salt solution were slowly dripped into them respectively, and stirred continuously. The pH of the suspension was controlled to 8±1 using a pH meter. After all the salt solutions were added, the suspension was moved into a constant temperature water bath, the crystallization temperature was controlled to 60°C, and stirred continuously for 10 h of crystallization. After the crystallization was completed, the solid-liquid separation was carried out, and the solid was washed with deionized water until neutral, and then the solid was placed in a 60°C constant temperature oven to dry for 12 h. The obtained catalyst precursor is a layered double metal hydroxide. The obtained solid powder is further treated with a structural topological transformation at 500 °C for 4 h and finally at 300 °C with a total flow rate of 100 mL min -1 , and reduced in a mixed gas of H2:N2 in a ratio of 1:4 for 2 h to obtain a layered multimetal hydroxide-derived copper-based catalyst Cu-S5 with an intercalated structure.

[0187] In the Cu-S5 catalyst provided in this embodiment, based on the mass of the catalyst being 100%, the mass content of Cu is 20 wt%, the mass content of Zn is 60 wt%, and the mass content of metal Al is 20 wt%.

[0188] The reaction product detection method is the same as that in Example 1, and the detection results are shown in Table 1.

[0189] 2. Cu-S5 catalyst for carbon dioxide hydrogenation

[0190] This method is the same as the method for catalytic hydrogenation of carbon dioxide provided in Example 1, except that the catalyst is the Cu-S5 catalyst provided in this comparative example, and the rest is the same as in Example 1. The test results are shown in Table 1.

[0191] Comparative Example 2

[0192] 1. Preparation of Cu-S6 catalyst

[0193] This comparative example provides a copper-based catalyst prepared by an impregnation method using a metal oxide of ZrO2 / ZnO / Al2O3 as a carrier, which is denoted as Cu-S5. The specific preparation method of the catalyst is as follows:

[0194] The ZrO2 / ZnO / Al2O3 oxide powder was added to 50 mL of copper nitrate trihydrate solution to maintain the same acid-base properties as the LDHs-based catalytic material, followed by ultrasonic treatment for 1 h, standing overnight, and after crystallization, solid-liquid separation was performed, and the solid was washed with deionized water until neutral, and then placed in a 60°C thermostat for 12 h. The obtained solid powder was further treated with structural topological transformation, treated at 500°C for 4 h, and finally at 300°C with a total flow rate of 100 mL min -1 , and reduced in a mixed gas of H2:N2 in a ratio of 1:4 for 2 h to obtain a copper-based catalyst Cu-S6.

[0195] In the Cu-S6 catalyst provided in this embodiment, based on the mass of the catalyst as 100%, the mass content of Cu is 20 wt%, the mass content of Zn is 65 wt%, the mass content of Zr is 5 wt%, and the mass content of metal Al is 20 wt%.

[0196] (ii) Cu-S6 catalyst catalyzes CO x (x=1 and / or 2) Hydrogenation

[0197] This method is the same as the method for catalytic hydrogenation of carbon dioxide provided in Example 1, except that the catalyst is the Cu-S6 catalyst provided in this comparative example, and the rest is the same as in Example 1.

[0198] The catalysts obtained in the above examples and comparative examples were tested. The reaction data of the preparation of methanol by hydrogenation of CO2 catalyzed by Cu-S1-Mg, Cu-S1-Sm, Cu-S1-Zr, Cu-S5 and Cu-S6 are shown in Table 1 (reaction pressure: 3 MPa, reaction space velocity: 9600 mL / g cat / h, reaction temperature: 200℃).

[0199] The reaction data of CO2 hydrogenation to methanol catalyzed by Cu-S2, Cu-S3 and Cu-S4 are shown in Table 2 (reaction pressure: 3 MPa, reaction space velocity: 80000 mL / g cat / h, reaction temperature: 220℃). The reaction data of CO hydrogenation to methanol catalyzed by Cu-S2, Cu-S3, and Cu-S4 are shown in Table 3 (reaction pressure: 4 MPa, reaction space velocity: 80000 mL / g cat / h, reaction temperature: 230℃).

[0200] The reaction data of hydrogenation of CO and CO2 mixed gas to produce methanol catalyzed by Cu-S2, Cu-S3 and Cu-S4 are shown in Table 4 (gas ratio: H2:CO:CO2:N2=4:1:1:1, reaction pressure: 4 MPa, reaction space velocity: 8000 mL / g cat / h, reaction temperature: 250℃).

[0201] Table 1

[0202]

[0203] Table 2

[0204]

[0205] Table 3

[0206]

[0207] Table 4

[0208]

[0209] Among them, CO x (x = 1 and / or 2) Reaction rate = (amount of CO / CO2 substance input into the system - amount of CO / CO2 substance in the system after reaction) / (time × catalyst mass);

[0210] CO x (x=1 and / or 2) Conversion rate = (amount of CO / CO2 substance in feed - amount of CO / CO2 substance in output) / (amount of CO / CO2 substance in feed)

[0211] Methanol selectivity = methanol production / CO2 consumption;

[0212] Methanol space-time yield = methanol production / (time × catalyst volume).

[0213] By comparing the reaction rate of carbon dioxide and the space-time yield of methanol of Cu-S1-Mg, Cu-S1-Sm, Cu-S1-Zr samples and Cu-S6 samples in Table 1, it can be seen that compared with the CuZnAlM-based catalyst prepared by non-layered polymetallic hydroxide precursors, the CuZnAlM-based catalyst based on the layered polymetallic hydroxide precursor has a significant improvement in the reaction rate and space-time yield of methanol from carbon dioxide hydrogenation, which indicates that the characteristics of the CuZnAlM-based catalyst prepared by the layered polymetallic hydroxide precursor are conducive to improving the catalytic reaction performance.

[0214] At the same time, by comparing the Cu-S1-Mg, Cu-S1-Sm, Cu-S1-Zr and Cu-S5 samples in Table 1, it can be seen that compared with the undoped CuZnAl catalyst, after doping with M element, the CO x(x=1 and / or 2) and the selectivity of methanol are also improved. According to the data in Table 2 and Table 3, the conversion rate and selectivity of preparing methanol by hydrogenation of CO or CO2 using Cu-S2, Cu-S3, Cu-S4, Cu-S5 and Cu-S6 samples are relatively high, indicating that the catalysts prepared by different methods can still achieve similar technical effects under different CO or CO2 feed gases, and the results are higher than those of the comparative examples of Cu-S5 and Cu-S6 samples.

[0215] It can be seen from the data in Table 4 that the catalytic reaction performance of methanol prepared from a mixture of CO and CO2 using Cu-S2, Cu-S3, Cu-S4, Cu-S5, and Cu-S6 samples is also relatively high, indicating that catalysts prepared by different methods can still achieve similar technical effects under the conditions of a mixture of CO and CO2 raw materials, and the results are all higher than those of the comparative examples of Cu-S5 and Cu-S6 samples.

[0216] In addition, according to the data in Tables 1, 2, 3 and 4, different doping elements, proportions and preparation methods will affect the catalyst structure, and thus the CO x (x = 1 and / or 2) and the selectivity of methanol are slightly different. It can be seen that the design of the CuZnAlM-based catalyst, a precursor of layered multimetal hydroxide, can not only effectively regulate the elemental composition ratio and control the structural topological transformation parameters, but also promote the CO2 adsorption activation ability by increasing the number of oxygen vacancies and alkaline sites, and improve the catalytic reaction performance by regulating the metal-support interaction. Therefore, a supported Cu-based catalyst with high dispersion of the active component Cu and controllable metal-support interface geometry and electronic properties is obtained, which has excellent performance and stability.

[0217] In summary, the preparation method of the layered multi-metal hydroxide precursor CuZnAlM-based catalyst of the present invention uses copper salt, zinc salt, aluminum salt, metal M salt as raw materials, hydroxide-containing alkaline compounds and carbonate aqueous solution or urea as precipitant, constant pH method, colloidal mill method, urea method (using acetone water washing) and hydrothermal synthesis method with alumina as aluminum source to prepare, and obtain the layered multi-metal hydroxide precursor CuZnAlM-based catalyst. The preparation method of the present invention utilizes the adjustable metal elements of hydrotalcite, and the active metal Cu in the catalyst obtained after the structural topological transformation (entropy change) is highly dispersed and still maintains the intercalation structure, thereby realizing the microstructure regulation of Cu in the Cu-based catalyst. By doping with different metals, the oxygen vacancy concentration and number, alkaline sites and Cu metal size in the catalyst are changed, thereby affecting the catalytic activity. In addition, the Cu in the layered multi-metal hydroxide precursor CuZnAlM-based catalyst prepared by different methods has good dispersion, and the electronic properties of the metal-support interface structure can be regulated, so it can be used for CO x (x=1 and / or 2) It also has good stability during hydrogenation reaction.

[0218] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A metal M-doped layered Cu-based catalyst, characterized in that: It includes an active component Cu and a carrier for supporting the active component Cu; The carrier includes Zn oxide, Al oxide and metal M oxide; The metal M is selected from any one or more of Mg, La, Ce, Sm, Zr, In, Ga, Sc, Y or Nd.

2. The metal M-doped layered Cu-based catalyst according to claim 1, characterized in that: The ratio of the molar amount of the divalent ions in the catalyst to the total molar amount of the divalent or higher ions is (1-6):1; In the catalyst, the doping amount of metal Cu is 0.1-90 wt%; In the catalyst, the doping amount of metal Zn is 0.1-80 wt%; In the catalyst, the doping amount of metal Al is 0.1-40 wt%; In the catalyst, the doping amount of metal M is 0.1-40 wt%.

3. The metal M-doped layered Cu-based catalyst according to claim 1 or 2, characterized in that: The metal M-doped layered Cu-based catalyst has a nano-scale layered structure.

4. A method for preparing a metal M-doped layered Cu-based catalyst as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1: mixing a copper source, a zinc source, an aluminum source, a metal M source and a solvent to obtain a mixed solution; S2: after mixing the precipitant with the mixed solution, a catalyst precursor of a layered multi-metal hydroxide is prepared by any one of a constant pH method, a colloid mill method, a urea-acetone method or a hydrothermal synthesis method; S3: subjecting the catalyst precursor obtained in step S2 to a structural topological transformation treatment and a reduction treatment to obtain a metal M-doped layered Cu-based catalyst.

5. The preparation method according to claim 4, characterized in that: The copper source includes any one or more of copper nitrate and its hydrate, copper chloride or copper acetate; The zinc source includes any one or more of zinc nitrate and its hydrate, zinc acetate or zinc chloride; The aluminum source includes any one or more of aluminum nitrate and its hydrate, aluminum chloride hexahydrate, anhydrous aluminum chloride or aluminum oxide; The magnesium source includes magnesium nitrate and its hydrate and / or magnesium chloride; The lanthanum source includes any one or more of lanthanum nitrate and its hydrate, lanthanum chloride, lanthanum sulfate or lanthanum oxide; The cerium source includes any one or more of cerium nitrate and its hydrate, cerium oxide, cerium chloride or cerium sulfate; The samarium source includes samarium nitrate and its hydrate and / or samarium chloride; The zirconium source includes any one or more of zirconium nitrate and its hydrate, zirconium oxynitrate or zirconium acetylacetonate; The indium source includes any one or more of indium nitrate and its hydrate, indium chloride, indium sulfate or indium oxide; The gallium source includes any one or more of gallium nitrate and its hydrate, gallium chloride or gallium oxide; The scandium source includes any one or more of scandium nitrate and its hydrate, scandium chloride or scandium oxide; The yttrium source includes any one or more of yttrium nitrate and its hydrate, yttrium chloride or yttrium oxide; The neodymium source includes any one or more of neodymium nitrate and its hydrate, neodymium chloride or neodymium oxide.

6. The preparation method according to claim 4 or 5, characterized in that: The precipitant is selected from urea or mixed alkali; The mixed alkali comprises a hydroxide-containing alkaline compound and / or a carbonate; the molar ratio of the hydroxide-containing alkaline compound to the carbonate is (0.1-5):1; The hydroxide-containing alkaline compound includes sodium hydroxide and / or potassium hydroxide; The carbonate includes sodium carbonate and / or potassium carbonate.

7. The preparation method according to claim 6, characterized in that: The molar ratio of the urea to the metal ions in the mixed solution is (7-28):1; The molar ratio of the carbonate in the mixed alkali to the metal ions in the mixed solution is (6-8):

1.

8. The preparation method according to any one of claims 4 to 7, characterized in that The temperature of the structural topological transformation treatment is 50-800°C; The time for the structural topology transformation treatment is 0.5 to 48 h.

9. The preparation method according to any one of claims 4 to 8, characterized in that The temperature of the reduction treatment is 150-800°C; The pressure of the reduction treatment is 0.1~10 MPa; The reduction treatment is carried out in a reducing atmosphere; The reducing atmosphere comprises a reducing gas and an optional protective gas; the reducing gas comprises any one or more of hydrogen, methane or ammonia.

10. The metal M-doped layered Cu-based catalyst according to any one of claims 1 to 3 or the metal M-doped layered Cu-based catalyst prepared by the preparation method according to any one of claims 4 to 9 in CO x (x=1 and / or 2) Application in the hydrogenation reaction to produce methanol.

Citation Information

Cited By

  • La-doped ZnFe-LDHs (layered double hydroxides) stable Cu nano-particle catalyst, preparation method thereof and application of La-doped ZnFe-LDHs stable Cu nano-particle catalyst in preparation of furfuryl alcohol through furfural hydrogenation

    CN121551041A

  • La-doped ZnFe-LDHs stabilized Cu nanoparticles catalyst, preparation method thereof and application of the catalyst in preparation of furfuryl alcohol from furfural by hydrogenation

    CN121551041B